MANAJEMEN MASJID (STUDI PENGELOLAAN MASJID AGUNG Al-AZHAR JAKARTA) - Nurhidayat Muh Said (Fakultas Dakwah dan Komunikasi, 2016)
The management of mosques is based on good planning. Not only serves as a place of worship, the mosque also builds and educates humans into believing and cautious human beings. The Prophet set up a mosque as a center of worship, settles matters and disputes in the mosque, as a center of education and teaching, organizing war strategies and tactics in mosques, Islamic information centers, social places, placed by state mall / treasury, or Muslim community cash, his poems in the mosque while defending the prophet, and marriage.